How Simian Virus 40 Hijacks the Intracellular Protein Trafficking Pathway to Its Own Benefit … and Ours - Toscano, Miguel G.; de Haan, Peter (Frontiers in Immunology, 2018)
Viruses efficiently transfer and express their genes in host cells and evolve to evade the host’s defense responses. These properties render them highly attractive for use as gene delivery vectors in vaccines, gene, and immunotherapies. Among the viruses used as gene delivery vectors, the macaque polyomavirus Simian Virus 40 (SV40) is unique in its capacity to evade intracellular antiviral defense responses upon cell entry. We here describe the unique way by which SV40 particles deliver their genomes in the nucleus of permissive cells and how they prevent presentation of viral antigens to the host’s immune system. The non-immunogenicity in its natural host is not only of benefit to the virus but also to us in developing effective SV40 vector-based treatments for today’s major human diseases.